1997
DOI: 10.1124/mol.51.5.741
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Enzymatically Active CYP3A4 by Caco-2 Cells Grown on Extracellular Matrix-Coated Permeable Supports in the Presence of 1α,25-Dihydroxyvitamin D3

Abstract: The human colon carcinoma cell line, Caco-2, is widely used as a model for oral absorption of xenobiotics. The usefulness of Caco-2 cells has been limited, however, because they do not express appreciable quantities of CYP3A4, the principle cytochrome P450 present in human small bowel epithelial cells. We report that treatment of Caco-2 cells with 1 alpha,25-dihydroxyvitamin D3, beginning at confluence, results in a dose- and duration-dependent increase in CYP3A4 mRNA and protein, with little apparent effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
206
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(223 citation statements)
references
References 56 publications
14
206
3
Order By: Relevance
“…In an exploratory part of this work, we found that 1␣,25-(OH) 2 D 3 is an inducer of CYP3A4 in human hepatocytes, as previously observed by others in intestinal cell lines (16,17).…”
supporting
confidence: 51%
See 2 more Smart Citations
“…In an exploratory part of this work, we found that 1␣,25-(OH) 2 D 3 is an inducer of CYP3A4 in human hepatocytes, as previously observed by others in intestinal cell lines (16,17).…”
supporting
confidence: 51%
“…Both NR1 and NR2 are imperfect DR4 motifs and essential for phenobarbital induction of CYP2B genes. In human CYP2B6, the phenobarbital-responsive element module is located between -1684 and -1733 and has been shown to bind to and be transactivated by CAR and by PXR (12, 15).Previous reports revealed that 1␣,25-dihydroxyvitamin D 3 (1␣,25-(OH) 2 D 3 ), the most active metabolite of vitamin D 3 , behaves as a transcriptional inducer of CYP3A4 in the colic carcinoma Caco-2 cell line and in the human intestinal LS180 cell line (16,17). Vitamin D 3 function is mediated through the vitamin D receptor (VDR; NR1I1), which, after binding 1␣,25-(OH) 2 D 3 with high affinity, forms heterodimers with .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we evaluated the expression of mRNA of CYP1A1 in Caco-2 cells, since CYP1A1 is expressed in the cells. 18) Figure 1 shows the CYP/GAPDH ratio of mRNA in non-treated, VD 3 -treated, and b-NF-treated Caco-2 cells. In non-treated Caco-2 cells, the expression of CYP1A1 mRNA was greater than that of any other CYP mRNA.…”
Section: Expression Of Mrna Of Cyps In Vd 3 -Or B B-nf-treatedmentioning
confidence: 99%
“…Much of this variability results from differences in CYP3A4 protein content, which can vary more than 8-fold even in mucosal epithelium obtained from healthy volunteers [1,2]. Although the source of that variability is probably multi-factorial, some studies have documented dynamic changes in CYP3A4 transcription that can occur following activation of the vitamin D receptor (VDR) by its natural ligand, 1α,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) [3,4,5,6]. The intestinal mucosa is an important target tissue for 1,25(OH) 2 D 3 , where it regulates the expression of calcium binding and transport proteins and helps maintain calcium homeostasis throughout the body [7,8,9].…”
Section: Introductionmentioning
confidence: 99%